2018
DOI: 10.1007/s00484-018-1530-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hot days on occupational heat stress in the manufacturing industry: implications for workers’ well-being and productivity

Abstract: Climate change is expected to exacerbate heat stress at the workplace in temperate regions, such as Slovenia. It is therefore of paramount importance to study present and future summer heat conditions and analyze the impact of heat on workers. A set of climate indices based on summer mean (Tmean) and maximum (Tmax) air temperatures, such as the number of hot days (HD: Tmax above 30 °C), and Wet Bulb Globe Temperature (WBGT) were used to account for heat conditions in Slovenia at six locations in the period 198… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 42 publications
1
41
0
1
Order By: Relevance
“…Mean surface temperature as well as the frequency and duration of heat waves have increased in the last decades in Europe (IPCC 2013), in particular in the south-east of the continent (Pogačar et al 2018; Barriopedro et al 2011;Morabito et al 2017). Also, future heat waves are very likely to be more frequent and longer-lasting (IPCC 2013), mainly as a direct consequence of the increase in mean temperatures (Schär, et al 2004;Fischer and Schär 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Mean surface temperature as well as the frequency and duration of heat waves have increased in the last decades in Europe (IPCC 2013), in particular in the south-east of the continent (Pogačar et al 2018; Barriopedro et al 2011;Morabito et al 2017). Also, future heat waves are very likely to be more frequent and longer-lasting (IPCC 2013), mainly as a direct consequence of the increase in mean temperatures (Schär, et al 2004;Fischer and Schär 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, during hot seasons, employees do not always recover sufficiently between working days. Individual factors such as age, weight, physical condition, alcohol and drug use, illnesses, and clothing affect heat-caused symptoms (Gatto et al, 2016;Marchetti et al, 2016;Pogačar et al, 2018).…”
Section: Osh Challenges Caused By Climate Changementioning
confidence: 99%
“…Many authors have suggested that more research is needed on climate change and its effects, such as regarding work performance, pesticides use, solutions to mitigate heat stress, and the long-term effects of infectious diseases (Gatto et al, 2016;Kjellstrom et al, 2016;Vonesch et al, 2016;Pogačar et al, 2018). Schulte et al (2016) proposed that follow-up, research, and risk assessment are needed to better understand and classify the connections between OSH and climate change.…”
Section: Future Studies In Summarymentioning
confidence: 99%
“…Such conditions directly affect human well-being and can develop into heat-related illnesses such as fatigue, muscle cramps and heat stroke. In the context of working people, several studies revealed the negative impact of heat stress on workers' health (Pogačar, et al, 2018) and labour productivity 10 (Kjellstrom, et al, 2009;Ioannou, et al, 2017). International organizations such as the International Standards Organization (ISO) and the US National Institute for Occupational Safety and Health (NIOSH) have developed guidelines to protect working people against heat stress (ISO, 1989;ISO, 2017;NIOSH, 2016).…”
Section: Heat Stress Indexmentioning
confidence: 99%